Characterization of blood dendritic and regulatory T cells in asymptomatic adults with sub-microscopic Plasmodium falciparum or Plasmodium vivax infection. (December 2016) - Kho, Steven; Marfurt, Jutta; Handayuni, Irene; Pava, Zuleima; Noviyanti, Rintis; Kusuma, Andreas; Piera, Kim; Burdam, Faustina; Kenangalem, Enny; Lampah, Daniel; Engwerda, Christian; Poespoprodjo, Jeanne; et al.
Abstract Background Plasmodium falciparum andPlasmodium vivax infections compromise dendritic cell (DC) function and expand regulatory T (Treg) cells in both clinical disease (malaria) and experimental human sub-microscopic infection. Conversely, in asymptomatic microscopy-positive (patent)P. falciparum orP. vivax infection in endemic areas, blood DC increase or retain HLA-DR expression and Treg cells exhibit reduced activation, suggesting that DC and Treg cells contribute to the control of patent asymptomatic infection. The effect of sub-microscopic (sub-patent) asymptomaticPlasmodium infection on DC and Treg cells in malaria-endemic area residents remains unclear. Methods In a cross-sectional household survey conducted in Papua, Indonesia, 162 asymptomatic adults were prospectively evaluated for DC and Treg cells using field-based flow cytometry. Of these, 161 individuals (99 %) were assessed retrospectively by polymerase chain reaction (PCR), 19 of whom had sub-microscopic infection withP. falciparum and 15 with sub-microscopicP. vivax infection. Flow cytometric data were re-analysed after re-grouping asymptomatic individuals according to PCR results into negative controls, sub-microscopic and microscopic parasitaemia to examine DC and Treg cell phenotype in sub-microscopic infection. Results Asymptomatic adults with sub-microscopicP. falciparum orP. vivax infection had DC HLA-DR expression and Treg cell activation comparable to PCR-negative controls. Sub-microscopicP. falciparum infection was associated with lower peripheral CD4+ T cells and lymphocytes, however sub-microscopicPlasmodium infection had no apparent effect on DC sub-set number or Treg cell frequency. Conclusions In contrast to the impairment of DC maturation/function and the activation of Treg cells seen with sub-microscopic parasitaemia in primary experimental humanPlasmodium infection, no phenotypic evidence of dysregulation of DC and Treg cells was observed in asymptomatic sub-microscopicPlasmodium infection in Indonesian adults. This is consistent with DC and Treg cells retaining their functional capacity in sub-microscopic asymptomatic infection withP. falciparum orP. vivax in malaria-endemic areas.